Literasi Pembiayaan Legal Sebagai Landasan Keharmonisan Keluarga: Studi Kasus di Nagari Pagaruyung - Yustiloviani Yustiloviani; Wardatun Nabilah; Deri Rizal; Siska Elasta Putri; Alfi Husni; Asrinaldi Asrinaldi; Suhatri Mariko (Universitas Negeri Padang, 2025)
This study examines the role of legal financing literacy in fostering family harmony and resilience within the community of Nagari Pagaruyung, Indonesia. Using a Community-Based Research approach and the Pentahelix collaboration model, the program integrates legal education, financial literacy training, and partnerships with formal financing institutions to strengthen lawful and sustainable economic practices. Activities include family-centered legal counseling, awareness campaigns on financial and legal risks, and empowerment of community and religious leaders as literacy agents. Data were collected via in-depth interviews with society members affected by illegal financing. Analysis assessed the impact of rentenir on family resilience, revealing significant improvements in household understanding of legal mechanisms, reduced reliance on illegal loans, and increased access to formal sharia services. This strengthened family communication, economic stability, and vulnerability reduction, enhancing social harmony.The findings reveal significant improvements in household understanding of legal financial mechanisms, a decline in reliance on illegal lending practices, and increased access to formal, sharia-compliant financing services. Strengthened family communication, economic stability, and reduced financial vulnerability contribute to greater social harmony and resilience. The study recommends the continuous integration of legal-financial literacy into community education and the reinforcement of multisectoral collaboration to sustain family well-being and financial inclusion.